OPTIMASI BIAYA PROSES KARENA VARIASI KECEPATAN DAN KEDALAMAN POTONG PADA POROS AISI-1040 MENGGUNAKAN MESIN BUBUT KNUTH DM-1000A - Jolly Victor Aseng; Jotje Rantung; Rudy Poeng (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
This research was aimed to optimize a lathing cost by varying the cutting speed and cutting depth. A test was perfomed on 27 steel shaft AISI-1040 test objects with diameter of 25 mm and 150 mm long each, in order to obtain the optimum cutting time and cost in a lathing process. It was found that higher the cutting speed, the lower the total production cost, while the cutting depth does not affect the total production cost. The optimum average machining time is 3.153 minute/test object and the lowest total production cost is Rp.5,653/test object. The optimization made the target to minimize the total production cost was reached in cutting speed of 1600 rpm and cutting depth of 1,00 mm, with total production cost of the lathing process of the 27 test objects as much as Rp.16,960 Keyword: Optimization, Lathe, Cutting time, Production cost